Predictive Automatic Relevance Determination by Expectation Propagation - Qi, Yuan (Alan); Minka, Tom; Picard, Rosalind W.; Ghahramani, Zoubin (ICML, 2004)
In many real-world classification problems the input contains a large number of potentially irrelevant features. This paper proposes a new Bayesian framework for determining the relevance of input features. This approach extends one of the most successful Bayesian methods for feature selection and sparse learning, known as Automatic Relevance Determination (ARD).